Transforming IT Services : Strategic Approaches and Lessons Learned - Roshan Lulla, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The paper reviewed relevant articles on strategic pursuit management. Being a conceptual paper, I have started by highlighting the overview / essence of strategic pursuit management and elaborating the role of Pursuit leader. This was followed by research and refereeing different proven strategies and factors that may lead to discussions on factors that affect strategy formulation, strategy implementation as well as factors bedeviling strategy implementation. Essentiality of strategic management practices as a radical improvement method was equally highlighted.
Keywords: Strategic Management; Strategy Planning